The Problem of Dynamic Regulation of Train Formation on a Marshalling Yard (Advances in Systems Science and Applications, 2024)
The problem of dynamic freight trains formation at a railway station is considered. This problem is part of a two-step strategy to create a dynamic train formation plan. It is assumed that technical routes of all cars and the predicted arrival time of new groups of cars at the station are known. The problem is to determine the set of cars and the departure time of each train formed at this station, taking into account the availability of locomotives and restrictions on the length of trains. The goal is to minimise the total waiting time for cars at the station. Mathematical models for different versions of the problem are presented as an integer and a mixed integer linear programming problems. Results of computational experiments allow to estimate the influence of the amount of information about arriving trains to the station on the value of the objective function.